Microsurgical Foot Reconstruction in Children Affected by Lawn Mower Injury - Sandra Feldler, MD; Sandra Scharfetter, MD; Lorenz Pisecky, MD; Manuel Gahleitner, MD; Gottfried Wechselberger, MD; Manfred Schmidt, MD, FEBOPRAS (Plastic and Reconstructive Surgery, Global Open)
Background:. Lawn mower injuries can cause limb-threatening wounds in the lower extremities of children. Although most cases require only basic wound treatment, a minority need microsurgical and orthopedic reconstruction for limb salvage. These procedures remain complex owing to small vessel diameter, increased vasospasticity, limited postoperative compliance, and continued growth in children. This case series demonstrated successful microsurgical foot reconstructions in a selected pediatric patient cohort. Methods:. Three patients younger than 5 years underwent foot reconstruction after mower injury. Injury patterns included (1) Chopart-like forefoot amputation, (2) first toe amputation, and (3) amputation of metatarsals I and II with destruction of the third toe, each with respective soft tissue defects. One patient required hindfoot reconstruction and tendon transfers before microsurgery. Two patients received latissimus dorsi flaps, and 1 was treated with a gracilis muscle flap. Functional outcomes were assessed using the Lower Extremity Functional Scale. Results:. Patients were aged 2, 3, and 5 years, with reconstruction performed 1–24 days postinjury. All 3 patients underwent successful microsurgical and orthopedic reconstruction with no major complications. All patients presented with preserved ability to walk and participate in sports, achieving Lower Extremity Functional Scale scores of 75–80 out of 80, even after a maximum follow-up of 20 years. Conclusions:. Foot reconstructions after traumatic foot amputation in children are intricate procedures. Nonetheless, microvascular reconstruction is a feasible option for limb salvage in pediatric patients even at ages as young as 2 years. Interdisciplinary cooperation is essential to provide a comprehensive treatment concept and restore optimal functionality.